PERSEPSI GURU PAMONG TERHADAP KETERAMPILAN MENGAJAR MAHASISWA PPL JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN AMBON DI MTs NEGERI BATUMERAH AMBON - Lela Bisugi; Idrus Sere; Saddam Husein (al-Iltizam: Jurnal Pendidikan Agama Islam, 2020)
Abstract The purpose of this study is to find out the perception of teachers pamong on teaching skills of students PPL Department of Islamic Education Faculty of Sciences Tarbiyah and Teacher Training IAIN Ambon On Madrasah Tsanawiyah Negeri Ambon. The type of research used is descriptive qualitative. This research was conducted from November 4 to December 4, 2019 with the location taken in this study in Madrasah Tsanawiyah Negeri Ambon. The informant in this research consists of 1 teacher Akidah Akhlak, 1 people teachers Fiqih and 1 teacher Al-Qur’an hadits. To analyze the data obtained through observations and interviews, as well as documentation, then the data obtained is analyzed using the data reduction stage (data reducation), data assessment (data display) and data conclusions (verification). The results of the research are related to the perception of pamong teachers on the teaching skills of PPL students of the Department of Islamic Education Faculty of Tarbiyah and Teacher Training IAIN Ambon MTs Negeri Ambon Years 2018, it is concluded that PPL students have been able to plan their learning well in accordance with the standards of the process, both the components and the principles of its preparation have been met. This is seen from the initial / preliminary activities, students in opening lessons are fairly good, but the most important aspect in the initial activity, namely conveying the objectives of learning, has been carried out well. In the core activities, students can already apply questioning skills, strengthening skills, and classroom management skills to core activities during the learning. And at the end/closing activities, PPL students have been able to close the lesson by preparing a summary of the material together, summarizing, and doing follow-up to the students. Keywords: Pamong Teacher Perception, Teaching Skills, PPL Students Majoring in Islamic Religious Education